2007
DOI: 10.1080/00016340701371322
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐symptomatic increase in urine‐orosomucoid excretion in pre‐eclamptic women

Abstract: Pre-eclampsia is associated with a pre-symptomatic increase in the urine excretion of orosomucoid, and orosomucoid excretion precedes that of albumin. Orosomucoid excretion can probably be used as a prognostic tool in combination with other screening methods, and seems to be a more sensitive marker for evolving pre-eclampsia than albumin. Plasma orosomucoid is significantly increased late in pre-eclampsia. Thus, the increased excretion of orosomucoid must primarily originate from altered renal processing of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(59 reference statements)
0
10
1
Order By: Relevance
“…We have previously shown that orosomucoid was excreted before albumin (9), and in the present study also before transferrin and IgG. The protein structure of orosomucoid is not solved, but based on molecular weight it is smaller than the other HMW proteins.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…We have previously shown that orosomucoid was excreted before albumin (9), and in the present study also before transferrin and IgG. The protein structure of orosomucoid is not solved, but based on molecular weight it is smaller than the other HMW proteins.…”
Section: Discussioncontrasting
confidence: 53%
“…Determination of other protein excretion patterns can help us to understand more about the underlying renal pathology in PE. We have previously shown that the small, negatively charged protein orosomucoid was excreted before albumin in PE pregnancies (9). To learn more about the renal changes in PE and healthy pregnancies, we analysed the protein excretion pattern of the high molecular weight (HMW) proteins immunoglobulin G (IgG) and transferrin and the low molecular weight (LMW) proteins α1‐ and β2‐microglobulins at six different time intervals from the 18th week of pregnancy until delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studies mentioned above, novel biomarkers such as urine orosomucoid, an acute phase protein, show promise in early prediction of preeclampsia (Kronborg et al 2007). To date, however, studies of potential biomarkers for predicting preeclampsia have involved relatively small numbers of patients, although many of the studies have ambiguous definitions of preeclampsia and unclear distinction of early and severe disease.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-1-acid glycoprotein is an acute phase protein that increases during inflammation and protects the endothelium. It was previously identified as a predictive biomarker for PE in urine [37,38]. Alpha-1-acid glycoprotein is constitutively expressed by human microvascular endothelial cells [39]).…”
Section: Other Differentially Abundant Proteins In Csf Of Patients Wimentioning
confidence: 99%